Development of Adolescent Well-Being Model in Malaysia: Analysis of Protective Factors in School - Bakar, Azlina Abu; Mohamad, Haslina; Kasim, Tengku Sarina Aini Tengku; Selamat, Taufiqnur; Hassan, Anuar Abu; Bakar, Noor Insyiraah Abu; Thurasingam, Vignes; Nordin, Mohammad Hazim Amir (International Journal of Membrane Science and Technology, 2023)
Well-being is a multidimensional construct that involves a state where individuals find peace, life needs are met, have a meaningful life, have life goals, autonomy, have a satisfactory quality of life in terms of physical, psychological and social. The partial least squares structural equation modelling (PLS-SEM) was employed to assess the research model using SmartPLS 4. This study was conducted on 587 teenagers. Among other factors measured in this study are resilience, relationship with school, parental involvement, self-efficacy, religiosity and spirituality. Among the instruments used in this study are Well-Being Scale, Spiritual Well-being, Religiosity Scale, Resiliency Belief Scale, Coppell's Self-Efficacy Scale, Parental Involvement Questionnaire and School Attachment Questionnaire. The items in this instrument are hypothesized as a priori and have non-zero loading for all dimensions in the model. The analysis of the items shows that the measurement model for all instruments is a well-fitting, multidimensional and reflective model. Data is also free of multicollinearity with good internal validity, convergent and discriminant validity. The results also demonstrate that resilience, school attachment, religiosity, parental involvement, self-efficacy altogether positively affected teenagers’ well-being (? = 0.158, ? = 0.193, ? = 0.154, 0.280, 0.345,p <0.01) respectively, except spirituality. The model explained 68 percent of the variance in well-being (R2=. 675) with AVE 0.70 and composite reliability 0.97. Analysis of the items resulted in a well-fitting model (SRMR<0.08, p<0.01). Therefore, well-being of young generation is significant to bring sustainable development to the mainstream and as protective factors against some of the challenges that may arise so that they have ability for self-regulation in emotions and become resilience. The promotion of well-being in teens can help mitigate the onset of negative effects of mental health.